Flora of springs in the Polish Tatra Mountains – habitat and phytosociological characteristics of crenophiles - Smieja, Agata (Biodiversity: Research and Conservation, 2015)
The flora of 179 springs in Tatra National Park was studied between 2003-2006. These springs represent complete diversity in the region with respect to altitude (from 900 to 1960 m a.s.l.), kind of bedrock (on siliceous and carbonate bedrock) and spring discharge (from 0.1 to >3500 l/s), and they also represent various ecomorphological types (mainly rheo- and helocrenes). In the springs, 239 plant taxa were recorded (60 mosses, 51 liverworts and 128 taxa of vascular plants). Among these species, 13 taxa (Arabis soyeri subsp. subcoriacea, Bryum schleicheri, Cardamine amara, Dichodontium palustre, Epilobium alsinifolium, E. anagallidifolium, Heliosperma quadridentatum, Palustriella commutata, Philonotis calcarea, P. seriata, Rhizomnium magnifolium, Scapania paludosa, S. uliginosa) had an ecological optimum in crenic habitats (crenophiles). Ecological and phytosociological characteristics of these species, as well as their distribution in the investigated springs, were shown.